On the Abolition of Academic Labour: The Relationship Between Intellectual Workers and Mass Intellectuality - Richard Hall (tripleC: Communication, Capitalism & Critique)
This article analyses the ways in which academic labour as a productive activity is subsumed inside the circuits and cycles of finance capital. These circuits are redefining universities as transnational associations of capitals, through which the concrete and abstract realities of academic labour are recomposed for value production and accumulation. One way of critiquing and moving beyond such a recomposition is through a reconsideration of academic labour as a fetishised form of labour, and subsequently framed in terms of the idea of “mass intellectuality”. The potential for mass intellectuality to enable liberation from the domination of capitalist social relations is contested, but the idea of socially-useful, living knowledge offers a mechanism for rethinking the value of academic labour, and pointing towards its abolition. Thus, the article asks whether it is possible to dissolve academic labour into the fabric of society as intellectual work, through which another image of society and social production becomes possible. Here the ideas of open co-operativism and fearless practice underpin a politics of alliance against capital that seeks to abolish the present state of things.